Derecho penal y protección de datos personales - Velasco Pérez, Zuleymi (2024)
The article analyzes the regulatory background of personal data in the Panamanian legal system; a comparative legislative study is carried out on digital rights in Latin America, as well as the problem of digital violence, criminal types and everything related to the right of access to justice in this area. As a contribution, the work examines the social roots of the problem and proposes a contemporary, clear explanation and a practical approach for the application of the rights of the holders of personal and sensitive data. Likewise, conceptual definitions are made to identify the elements that build the link between inalienable rights, new technologies and criminal justice, and the different jurisprudential currents in Panama in relation to criminal law and the protection of personal data are exposed.